The right choice of sports training in the treatment of diseases - Turdiyev Shuxrat Berdiyevich (Euro Asian Journal Publishing, 2024)
This article explores the efficacy of sports training in the treatment of various diseases. It delves into the existing literature to analyze the impact of exercise therapy on different medical conditions. Through a methodical review, the article aims to highlight the benefits, methods, and outcomes associated with incorporating sports training into disease management strategies.
Keywords: Sports training; disease management; exercise therapy